A functional extracellular matrix biomaterial enriched with VEGFA and bFGF as vehicle of human umbilical cord mesenchymal stem cells in skin wound healing. (24th November 2021) - Xu, Zhongjuan; Cao, Junjun; Zhao, Zhe; Qiao, Yong; Liu, Xingzhi; Zhong, Junjie; Wang, Bin; Suo, Guangli
Abstract: The construction of microvascular network is one of the greatest challenges for tissue engineering and cell therapy. Endothelial cells are essential for the construction of network of blood vessels. However, their application meets challenges in clinic due to the limited resource of autologous endothelium. Mesenchymal stem cells can effectively promote the angiogenesis in ischemic tissues for their abilities of endothelial differentiation and paracrine, and abundant sources. Extracellular matrix (ECM) has been widely used as an ideal biomaterial to mimic cellular microenvironment for tissue engineering due to its merits of neutrality, good biocompatibility, degradability, and controllability. In this study, a functional cell derived ECM biomaterial enriched with VEGFA and bFGF by expressing the collagen-binding domain fused factor genes in host cells was prepared. This material could induce endothelial differentiation of human umbilical cord mesenchymal stem cells (hUCMSCs) and promote angiogenesis, which may improve the healing effect of skin injury. Our research not only provides a functional ECM material to inducing angiogenesis by inducing endothelial differentiation of hUCMSCs, but also shed light on the ubiquitous approaches to endow ECM materials different functions by enriching different factors. This study will benefit tissue engineering and regenerative medicine researches.